1982
DOI: 10.1080/02791072.1982.10471907
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacosexology: The Effects of Drugs on Sexual Function – A Review

Abstract: The literature on the sexual side effects of drugs and chemicals has been reviewed. There are many substances which alter the human sociosexual response cycle either negatively, positively or both. Many of the drugs used therapeutically have been reported to have adverse effects on sexuality, and this must be taken into account when these drugs are used clinically. Many substances which are used for recreational purposes (or sometimes abused) also have profound effects on sexual response. Many of these substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0
4

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(86 citation statements)
references
References 231 publications
(264 reference statements)
0
82
0
4
Order By: Relevance
“…New or infrequent cocaine users may report that cocaine induces spontaneous erection and ejaculation. 65 However, other research reported that ambiguous findings of cocaine's impact on sexuality might be due to variation in the dosage, route of administration or other factors. 66 MacDonald et al found that of men who had used cocaine for 1 year or longer, 66% reported to have erection difficulties.…”
Section: ) Cocainementioning
confidence: 99%
“…New or infrequent cocaine users may report that cocaine induces spontaneous erection and ejaculation. 65 However, other research reported that ambiguous findings of cocaine's impact on sexuality might be due to variation in the dosage, route of administration or other factors. 66 MacDonald et al found that of men who had used cocaine for 1 year or longer, 66% reported to have erection difficulties.…”
Section: ) Cocainementioning
confidence: 99%
“…14 Drugs which signi®cantly decrease testosterone synthesis or block utilization have been associated with decreased libido. 15 LHRH analogues reduce serum testosterone levels, while antiandrogens competitively inhibit the binding of testosterone and dihydrotestosterone to the androgen receptor thereby blocking the stimulatory activity of the two steroidal androgens. Steroidal antiandrogens also inhibit LHRH secretion resulting in a reduction of testosterone secretion.…”
Section: Figurementioning
confidence: 99%
“…The relationship between alcohol, drugs, and sexual function is very complex [2]. The problem of moral violations as described can not be approached only from one aspect, because reproductive health is affected and influences social systems and is closely related to values, morals, religions and cultures.…”
Section: Introductionmentioning
confidence: 99%